Resiliensi keluarga melalui pemberdayaan ekonomi peran ibu di masa pandemi - Wangsa, Ignasius Heri Satrya; Riyanto, Agustinus; Tyra, Maria Josephine; Lina, Lina; Onny, Johan Gunady; Parwati, Maria Ignasia Galuh (Jurnal Abdimas Musi Charitas, 2021)
ABSTRACT The present pandemic has changed the global economic life. In the family level it results the decreasing family income. This situation weakens the resilience. Therefore. it is urgent to create new opportunities within the context of family. Family has played major role where the mother’s involvement is significant to respond the change and to creatively look for entrepreneurship opportunity. This community service aims at improving the family resilience through economic empowerment of mother’s role. The activity is divided into two sessions, namely: (1) Practical skills of child independence development; and (2) Practical entrepreneurship skills “how to make peach gum herbal drink”. Survey was conducted at the end of the activity. One-Sample Test was employed to measure means value of perceived-benefit, involvement and loyalty which is accounted for 4 (= Agree) (Sig. > 0.05). Procedures for Bivariate Correlation to measure the participation level was applied. The result shows significant correlation between Session Attractiveness (KTM) and Perceived-benefit (PMM) (0.548/Sig. 0.01), and between Future Intention (KKG) and Recommendation (KR) (0.447/Sig. 0.05). Keywords: family resilience, entrepreneurship